Case report: Clonal evolution analysis of a rare case of meningioma lung metastases identifies actionable alterations in matched longitudinal tumour samples - Cosgrove, Nicola; Fitzpatrick, Orla M.; Grogan, Liam; Hennessy, Bryan T.; Furney, Simon J.; Toomey, Sinead (Frontiers in Oncology, 2025)
Metastatic meningioma is rare, occurring in less than 1% of patients, and very few case studies have been reported, in particular for those that have spread to the lungs. Here we describe a rare case of metastatic meningioma to the lungs. Following a discussion at a medical oncology multi-disciplinary team meeting, whole genome sequencing was requested in November 2021 and discussed at a neurosurgical molecular tumor board in June 2022. Sequencing was performed on matched longitudinal collected samples of the primary tumor resection, the re-excised recurrent tumor after adjuvant radiation therapy, the lung metastases before treatment with sunitinib, and one paired blood sample for tumor-normal analysis. Whole genome characterization and clonal evolution analysis confirmed neurofibromatosis 2 (NF2) gene loss as the main driver of this cancer. In the same cancer clone as NF2, we identified a BRCA2 (p.E51K) mutation was present in all tumors, which may represent a potential driver event, though evidence supporting this is currently limited. Although this mutation is predicted to potentially influence homologous recombination, its clinical relevance as a biomarker for PARP inhibition remains speculative and requires further investigation. We also noted a SETD2 (p.S1885N) mutation that was present only in the recurrent tumor which was identified as a predicted biomarker of response to WEE1 inhibition. There was a stepwise increase in tumor mutational burden (TMB) from the primary meningioma to lung metastases, suggesting this patient may have been a candidate for immunotherapy.